2000
DOI: 10.1016/s0360-1323(99)00029-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of an architectural design alternative (transoms) on indoor air environment in conventional kitchens in Taiwan

Abstract: This study investigates indoor air environment via the flow fields, temperature fields and air contaminants (carbon monoxide) distributions in conventional residential kitchens, and looks for effective methods to solve those problems through natural ventilation techniques. Numerical simulations of the physical problem under consideration have been performed via a finite volume method for solving the governing equations and boundary cond itions. It is obvious that location of accumulation of air contaminants is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 1 publication
0
33
0
1
Order By: Relevance
“…This numerical data makes it possible to analyze the hood capability and its disposition in the room. In fact, the main goal of a hood is to improve air quality in kitchens, which in some regions of the world is even suspected to be the cause of lung cancer due to the presence of oil-aerosol and gaseous contaminants [11].…”
Section: Full-scale Kitchen Model With Exhaust Hood Systemmentioning
confidence: 99%
“…This numerical data makes it possible to analyze the hood capability and its disposition in the room. In fact, the main goal of a hood is to improve air quality in kitchens, which in some regions of the world is even suspected to be the cause of lung cancer due to the presence of oil-aerosol and gaseous contaminants [11].…”
Section: Full-scale Kitchen Model With Exhaust Hood Systemmentioning
confidence: 99%
“…A number of approaches [2]- [4] were proposed to reduce the noise level in the kitchens, including the high-cost noise cancellation with a digital signal processor [2], [3]. The noise cancellation technology also carries extra devices on the range hood to make it bulky.…”
Section: Introductionmentioning
confidence: 99%
“…Natural ventilation could be achieved using architectural elements that are acceptable to cooks without affecting cooking practices to develop a fail-safe design (i.e., if all ventilation modes fail, an alternative mechanism exists to maintain indoor air quality). Chiang et al [15] performed computational fluid dynamics (CFD) simulations of the air environment in kitchens. The results indicated that the closer the transom was to the region with high carbon monoxide concentrations, the better it affected the natural ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical ventilation (by the operation of a hood or an exhaust fan) [4][5][6][7][8][9][10][11][12][13][14] or natural ventilation (e.g., opening the kitchen window) [15][16][17][18][19] can usually be employed to control kitchen air quality. The contrasting needs for thermal comfort and indoor air quality management by ventilation should be taken into consideration [20].…”
Section: Introductionmentioning
confidence: 99%